Perlindungan Hukum Terhadap Perempuan Sebagai Korban Penganiayaan Dalam Hubungan Pacaran Di Polres Gorontalo Kota - Nur Fajri Fauziah Pantu; Dr. Dian Ekawaty Ismail, S.H.,M.H; Jufryanto Puluhulawa, S.H., M.H (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out what factors cause women to become victims of abuse in dating relationships in Gorontalo City and how legal protection is for women as victims of abuse in dating relationships at the Gorontalo City Police Department. This research uses empirical legal research methods which are carried out by collecting data through observation and interviews. The results of this research show that abuse in dating relationships in Gorontalo City is a very worrying phenomenon and can have a negative impact on victims and society as a whole. Abuse in dating relationships in Gorontalo City involves various factors, both internal factors such as a high level of emotional dependence, low levels of victim self-confidence, and the victim's tendency to justify aggressive behavior from their partners, while external factors occur due to the influence of the social environment. , norms and culture, the influence of the environment where violence occurs, and position and power. The suggestion in this research is that the Government, especially the Regional Office of the National Land Agency in Gorontalo Regency, continues to strive to carry out more outreach to the people of Hutuo Subdistrict to carry out land registration so that they can have a certificate to obtain legal certainty. The legal protection provided by the Gorontalo City Police for victims of abuse in dating relationships is carried out by providing priority and quick responses to reports of abuse, collecting supporting evidence by conducting investigations into cases of abuse in dating relationships, such as witness statements, and physical evidence. The Gorontalo City Police also provides physical protection such as giving a detention order against the perpetrator and providing a safe space for the victim and maintaining the confidentiality of the victim's personal information to prevent further threats from the perpetrator.